Design and Development of a Compact and Vialess Microstrip Ultra-Wideband Bandpass Filter - Razalli, Mohammad Shahrazel (2009)
In radio frequency and microwave systems, filters are the most essential component to select the required signals. They are built together with other components such as mixers, amplifiers, oscillators and switches. Filters work by blocking the unwanted signals and allowing the desired signals through them before feeding it into other components or devices. In the latest interest and future radio frequency and microwave high speed communication technology like Ultra-Wideband (UWB), a bandpass filter with large bandwidth (> 500 MHz) is required to fulfill the specifications. This is due to the UWB format signal which uses very short time pulse wave within 1.0 ns to 0.1 ns. This thesis presents theories, methods, parameters, simulations and measurements of designed and development of bandpass filters to support UWB communication systems. There are four types of bandpass filters which are designed and developed to operate within 3.1 GHz to 10.6 GHz to support the UWB frequency range specification.Initially, the designed model is derived from J-inverter which it is a transformation of low pass to bandpass Chebyshev filter. Type of response is chebyshev since it is able to perform an equal-ripple return loss response in the whole passband. The equal-ripple return loss response can keep the insertion loss almost flat in the whole pass band and sharp-out-of-band rejection response. In the thesis, bandpass filters are designed and developed based on five poles quarterwavelength short-circuited stubs model. The model is theoretically capable to expand the frequency bandwidth by tuning its h (interior admittance level of the stubs) factor. The related mathematical equations are applied into mathematical software to speed up the optimization of h factor and obtain the required admittance level for stubs and transmission lines. The first bandpass filter has successfully shown the expansion in frequency bandwidth to support Ultra-wideband specifications. The filter uses five vias to short-circuit stubs to the ground. Stubs, transmission lines admittance and h are tuned slightly to expand the fractional bandwidth (FBW) more than 100 %. The measured scattering parameters are |S21| = 1.27 dB and S11 = -7.8 dB respectively. The second bandpass filter is improved by reducing the short-circuited via elements. First and second stubs are shared on the first via while fourth and fifth stubs share on the third via. Only third stub has its own via thus creating new transformation filter shape nicknamed as “Butterfly”. This new shaped has 109 % of measured fractional bandwidth, lower scattering parameters |S21| which is below than 0.85 dB and S11 is better than -11.6 dB. Besides, it also reduces the number of via insertion in microstrip fabrication process.The third bandpass filter has totally eliminates vias and thus simplifies the microstrip fabrication process. Vias are replaced by microstrip patched capacitors. At microwave frequencies, these capacitors are parasitic elements and their parameters contribute to the successful performance in S-parameters measurement. The measured scattering parameters |S21| and S11 are better than 1 dB and -16.9 dB respectively. The fourth filter is improved in terms of scale dimension and group delay compares to the third filter. The structure is via-less and the filter uses less microstrip patch capacitors to perform compact size with “Butterfly” shape. By reducing microstrip patched capacitors, the filter shows better S-parameters measurements in the UWB passband with the lowest scattering parameters |S21| 0.53 dB and S11 of -14.8 dB. The group delay varies minimum within 0.47 ns in the whole UWB pass band.